Transformasi Pangan Lokal Berbasis Beras melalui Inovasi Produk Rice Crunchy sebagai Camilan Tradisional Modern - Ismi Soleha Nur Ameliani; Rahmi Rismayani Deri; Usi Nurulsita; Ikhwan Agil Maulana; Januar Huan Azmi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to create innovation in local rice-based food products by developing Rice Crunchy as a traditional snack with a modern touch, as well as to evaluate its characteristics and consumer acceptance. The research employed an experimental approach using a simple Research and Development (R&D) method, which included stages of raw material identification, product formulation, production process, and evaluation of product characteristics and consumer acceptance. Product evaluation was conducted through an organoleptic test involving 50 untrained panelists, assessing parameters of color, taste, texture, and overall preference using a 1–5 hedonic scale. The results showed that Rice Crunchy had a crispy texture, a slightly brownish white color, a distinctive rice aroma, and a sweet and savory taste. The organoleptic test results indicated that most panelists gave scores of 4 and 5 for each evaluation parameter, suggesting a high level of consumer acceptance. In addition, the use of plastic pouch packaging was considered effective in maintaining product quality and enhancing visual appeal. Therefore, the Rice Crunchy product innovation has the potential to become an alternative local food-based snack that can increase the added value of rice commodities while supporting food diversification.